2010
DOI: 10.24200/jams.vol15iss0pp9-14
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Omani Native Sheep Fiber Production and Quality Characteristics

Abstract: Wool production and quality measurements were carried out on 100 Omani native female sheep (body weight 38.6 ± 5.5 kg; age 993 ± 488 d). Sheep were kept in partially shaded pens and fed ad libitum Rhodes grass hay (crude protein 8.83%) plus a daily amount of 200 g general ruminant concentrate (crude protein 16.5% DM). Animals were shorn once a year and samples were taken from the left mid-side site to determine fleece and fiber characteristics. The scanning electron microscope (SEM) was used to study the fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…However, the densities were lower than those determined by Özfiliz (1992) in Karacabey Merino sheep, by Zık et al (1999) in Karayaka sheep, and by Kocamış and Aslan (2004) in Tuj sheep. The average primary follicle densities were similar to the Lori (Abbasi et al 2008), Afshari, Zandi, Mehrabani, and Balouchi (Ansari-Renani et al 2011) breeds of Iran, which is one of the most important sheep-breeding countries in the region, but were significantly lower than those of the Omani Native breed (Mahgoub et al 2010). The average secondary follicle densities of the Karakaş,Norduz,and Zom sheep (8.42 ± 1.48,8.51 ± 1.54,and 6.36 ± 1.44) (table 1 and figure 3) were similar to those determined by Batu and Özcan (1962) in White Karaman and Kıvırcık sheep and by Özcan in İvesi and Karakaya sheep (FAO 1986).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, the densities were lower than those determined by Özfiliz (1992) in Karacabey Merino sheep, by Zık et al (1999) in Karayaka sheep, and by Kocamış and Aslan (2004) in Tuj sheep. The average primary follicle densities were similar to the Lori (Abbasi et al 2008), Afshari, Zandi, Mehrabani, and Balouchi (Ansari-Renani et al 2011) breeds of Iran, which is one of the most important sheep-breeding countries in the region, but were significantly lower than those of the Omani Native breed (Mahgoub et al 2010). The average secondary follicle densities of the Karakaş,Norduz,and Zom sheep (8.42 ± 1.48,8.51 ± 1.54,and 6.36 ± 1.44) (table 1 and figure 3) were similar to those determined by Batu and Özcan (1962) in White Karaman and Kıvırcık sheep and by Özcan in İvesi and Karakaya sheep (FAO 1986).…”
Section: Discussionsupporting
confidence: 56%
“…The values were also lower than those of the Karacabey Merino (Özfiliz 1992), Karayaka (Zık et al 1999), and Tuj (Kocamış and Aslan 2004) sheep but were higher than those reported by Tuncer and Cengiz (2009) The average S/P ratios of the Karakaş, Norduz, and Zom sheep (2.71 ± 0.70, 2.79 ± 0.69, and 1.85 ± 0.36) (table 1 and figure 4) were lower than those of the White Karaman, Dağlıç, Anatolian Merino (Batu and Özcan 1962), Karacabey Merino (Artan 1988(Artan , Özfiliz 1992, and Karayaka ( Zık et al 1999) sheep and similar to the ratios of the Kıvırcık (Batu andÖzcan 1962, Artan 1988), İvesi (Özcan 1965) and Karakaş and Norduz (Tuncer and Cengiz 2009) sheep. The average S/P ratios were similar to the Lori (Abbasi et al 2008), Afshari, and Mehrabani (Ansari-Renani et al 2011) sheep, lower than those of the Zandi, Lori, and Balouchi (Ansari-Renani et al 2011) sheep, and higher than those of the Omani Native (Mahgoub et al 2010) and Bakhtiari (Mobini 2012) sheep.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, coat length, thickness and hair density also affect the adaptive nature of animals in tropical regions, where short hair, thin skin and fewer hair follicles per unit area are directly linked to higher adaptability to hot conditions ( Figure 3). Indigenous sheep breeds adapted to arid and semi-arid regions possess morphological characteristics such as carpet type wool, which helps to provide better protection from direct solar radiation, and this type of wool also allows effective cutaneous evaporative heat dissipation (Mahgoub et al, 2010). The fat tail observed in sheep is also recognized as a morphological adaptation for better heat transfer (Gootwine, 2011).…”
Section: Morphological Responsementioning
confidence: 99%
“…The lambs were born during the spring and were evaluated subjectively for pelt traits (curl type, curl breadth, pattern, luster, color, and final pelt score) by a pelt assessor according to the method described in the guidelines of the Karakul Pelt Assessment Committee of Iran (7). Based on these guidelines, the score of curl breadth in different colors of pelt ranges between 5 and 10 (a score of 5 denotes inferior while a score of 10 denotes excellent), along with scores for luster (5-10), pattern (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), pelt size (0-5), skin thickness (0-5), and curl type , and then the final score of the pelt based on the scores given to the above characteristics is given to the lamb.…”
Section: Methodsmentioning
confidence: 99%